Інформаційні війни та їх вплив на суспільство - Морушко, Олександр; Бобришева, Поліна (Видавництво Львівської політехніки, 2025)
This study examines modern information warfare as a powerful tool for influencing society. It analyzes the mechanisms of disinformation dissemination, manipulation of public opinion, and the role of social media in shaping the information space.
Keywords: дезінформація; пропаганда; маніпуляція свідомістю; соціальні мережі; психологічний вплив